Honduras launches its first adaptive social protection policy, grounded in community evidence - Taiwo, Ibukun (2025)
Honduras has launched its first Adaptive Social Protection Policy, informed by community evidence from across the country. The policy strengthens how social protection systems anticipate and respond to climate, disaster, displacement, and economic shocks affecting the most vulnerable households.